PERLINDUNGAN HUKUM BAGI KONSUMEN TERKAIT PEMBATALAN SEPIHAK PENERBITAN TIKET PESAWAT OLEH PT. TRINUSA TRAVELINDO INDONESIA MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Dzakiannisa Roskiyasa; N.G.N Renti Maharaini Kerti (Fakultas Hukum Universitas Trisakti, 2019)
Legal protection for consumers is important, because without a balance of legal protection between consumers and business actors causes consumers to be in a weak position. With the development of e-commerce, online travel agents began to emerge, one of which was Traveloka. Based on this, the authors propose the problem of how the legal protection provided by the UUPK to consumers and how form Traveloka's responsibility as a business actor in the case of unilateral cancellation of aircraft ticket issuance sold on its website. This study uses a research method with a type of normative legal research with the nature of descriptive research and analyzed qualitatively, as well as conclusions based on deductive mindset. Based on the results of the analysis, the authors do that, legal protection of consumers has been regulated both preventively and repressively by Law Number 8 of 1999 concerning Consumer Protection. The form of business actor's responsibility in the form of a Contractual Liability based on a contract that has occurred between Traveloka and consumers, therefore Traveloka is obliged to provide compensation in the form of refunds or replacement of goods and / or services of similar or equivalent value to a Jakarta-Singapore Jetstar Air flight ticket based on the determination of the court Number 615 / Pdt.G / 2017 / PN.Jkt.Brt.Key Words : Consumer Protection, Business Actor’s Liability